Copepod production in the southern Benguela system - Hutchings, L.; Verheye, H. M.; Mitchell-Innes, B. A.; Peterson, W. T.; Huggett, J. A.; Painting, S. J. (ICES journal of marine science, 1995)
Several methods have been used to indirectly estimate copepod production in the southern Benguela region, based on field sampling of copepod stages and laboratory measurements of growth and development rates under variable food and temperature regimes. Estimates of production have steadily increased from 11 gC m−2 y−1 in 1979 to 80 gC m−2 y−1 in 1987. Since 1988, extensive measurements of copepod egg production and moulting rates of Calanus agulhensis at sea during hydro-acoustic fisheries surveys over the south and west coasts of South Africa in November have provided more direct estimates of copepod production. Daily Mean Production: Mean Biomass (P: B) ratios varied between 0.1 and 0.3 and annual production ranged between 17 and 150 gC m−2 y−1 Copepod biomass, distribution, and demographic structure varied between cruises in different years, apparently linked to both the abundance of predators and shifts in hydrology. Production appeared to be due more to shifts in distribution of biomass and demography of Calanus than to variations in growth rates. Poor correlations existed between juvenile growth and female egg production, suggesting one is unable to predict population growth from egg production rates only. Weak correlations between growth rates of different stages also suggest that the only meaningful measure of copepod production requires all stages to be incubated.